EVALUATING THE RELATIONSHIP BETWEEN LEAN MANUFACTURING DIMENSIONS AND RADICAL PRODUCT INNOVATION IN THE JORDANIAN PHARMACEUTICAL SECTOR - Al Hasan, Rima; Al-Zu’bi, Zu’bi M.F. (European Scientific Journal, ESJ, 2014)
The purpose of this study is to evaluate the relationships between lean manufacturing dimensions and radical product innovation in the Jordanian Pharmaceutical Sector. These dimensions entailcontinuous improvement, waste minimization, lean job characteristics and employees’ involvement. In order to achieve this objective, this study used a survey-based questionnaire as a data collection method. 164 questionnaires were gathered from 10 Jordanian Pharmaceutical manufacturers, and multiple regressionswere used to evaluate the relationships between the dependent and the independent variables.The findings revealed that continuous improvement and waste minimization dimensions have no statistically significant effect on radical product innovation, while the other two dimensions; lean job characteristics and employees’ involvement have statistically significant relationships with radical product innovation. Moreover, the analysis results showed that employees’ involvement has the greatest effect on radical product innovation.These results highlighted the importance of the human side in radical innovation and clarify different direction of the relationships between lean manufacturing dimensions and radical product innovation. Based on theseresults, many recommendations were suggested, one of them is to increase employees’ involvement in decision making process that is related to the production process, to enhance their ability to innovate.